Influence of Family and Friends Level of Social Support on Psychological Symptoms Among the Older Adults in Nigeria - Oluwaseyi Isaiah Olabisi MPH, MSc Nursing, RN, RPN; Joel Faronbi RN, Phd; Peter Adedeji MSc Nursing, RN; Grace Ademuyiwa MPH, RN; Yusuf Gambari MSc Nursing, RN; Aishat Lasisi BNSc, RN (SAGE Publishing, 2023)
Introduction Numerous studies have established the importance of social support on psychological symptoms among older adults, however, the distinct contribution of different levels of family and friends' social support has not been thoroughly assessed . Objectives This study determined the contribution of different levels of friend and family social support (high, moderate, low) on psychological symptoms among the older adult s. Methods A cross-sectional study was conducted among 538 older adults attending outpatient clinic s at two selected teaching Hospitals in Nigeria from February to July, 2021.The data was collected using the 7-item Generalized Anxiety Disorders Scale, Patient Health Questionnaire (PHQ-9), and the Multidimensional Scale of Perceived Social Support. The data was analyzed with SPSS version 23 and logistic regression was used for the inferential analysis. Results Older adults with moderate social support from family were 3.6 more likely to have depression symptoms than those with high family social support (AOR = 3.623, 95%CI 1.275-2.875, P  = .020). Also, those with moderate family social support (AOR = 2.875, 95%CI 2.425-11.875 , P  = .002), low family social support (AOR = 2.966, 95%CI 1.312-3.875, P  = .007), and low friends social support (AOR = 2.966, 95%CI 1.312-3.875, P  = .009) were more likely to have anxiety symptoms than those with high social support. Conclusion High social support confers a protective measure against depression and is effective in reducing psychological symptoms among older adults.